USA-Mexico border wall impedes wildlife movement - Harrity, Eamon J.; Traphagen, Myles; Bethel, Meagan; Facka, Aaron N.; Dax, Michael; Burns, Emily (Frontiers in Ecology and Evolution, 2024)
Geopolitical boundaries can present challenges to wildlife conservation because of varying environmental regulations, and increasingly, the existence of border barriers. As of 2024, approximately 1,023 km of border walls (i.e., steel bollard walls 5.5-9.1 m tall with interstitial spaces ≤10 cm) and 169 km of vehicle barriers (i.e., variable steel structures designed to stop vehicles but not pedestrians) exist along the USA-Mexico border. Some small wildlife passages (21.5 x 27.8 cm) were installed in border walls but few other accommodations for wildlife connectivity exist. As such, ecological consequences of border barriers may be severe and documenting the ability of wildlife to traverse these barriers will be essential to conservation efforts. We placed 36 wildlife cameras across 163.5 km of the USA-Mexico border in Arizona, USA and Sonora, MX to evaluate crossing rates through border barriers for 20 terrestrial species. We observed 9,240 wildlife events, including 1,920 successful crossing events. All focal species crossed through vehicle barriers, whereas white-tailed deer, mule deer, American black bear, American badger, wild turkey, and mountain lion appeared unable to cross through interstitial spaces in border walls. Small wildlife passages improved crossing rates for several species, including American badger, collared peccary, coyote, and mountain lion. Yet, small wildlife passages were scarce with only 13 along >130 km of continuous border wall and failed to allow American black bear, deer, and wild turkey to cross. Additional research on the impacts of border barriers and potential mitigation strategies will be critical for effective transboundary conservation.